Differential effects of salient visual events on memory-guided attention in adults and children - Nussenbaum, K; Scerif, G; Nobre, A (Wiley, 2018)
Both salient visual events and scene-based memories can influence attention, but it is unclear how they interact in children and adults. In Experiment 1, children (N = 27; ages 7-12) were faster to discriminate targets when they appeared at the same versus different location as they had previously learned or as a salient visual event. In contrast, adults (N = 30; ages 18-31) responded faster only when cued by visual events. While Experiment 2 confirmed that adults (N = 27) can use memories to orient attention, Experiment 3 showed that, even in the absence of visual events, the effects of memories on attention were larger in children (N = 27) versus adults (N = 28). These findings suggest that memories may be a robust source of influence on children's attention.